PROGRAM CN295 PROJECT MANAGEMENT ANALYSIS AND IMPROVEMENT STRATEGY FOR PRODUCTION OF A CUSTOMIZED MEDIUM AIRCRAFT (Case Study at Indonesian Aerospace) (The Indonesian Journal of Business Administration, 2019)
Where in carrying out its duties as PM for the CN295 Program, there are many obstacles if not managed properly it can lead to delayed delivery targets of aircraft to the customers. It is therefore necessary to determine a parameter that can be measured so that the work of the PM can be done categorically so that it can be measured the success rate of the project being executed. This can cause losses for PTDI who have to pay penalties due to late delivery to the customer. Because develop the aircraft is a sequential process, then being late in one function will cause other functions to wait, this is what makes the project late. By using the Current Reality Tree (CRT) method, the rootcause of the problems that occur in PTDI can be identified accurately.By using the Project Management reference from PMI in the form of PMBOK guide 5th edition, the solution to the rootcause that arise will be tried to be resolved. The business processes in PTDI actually exist in part that are similar to the principles of Project Management from PMBOK, so this paper will improve existing business processes and add processes that do not yet exist of the problems that have an impact on PTDI, it has a profound effect on the company's cashflow, operations, and also the welfare of PTDI's work. For this reason, the results of this case study will be proposed to the PTDI management so that it can be adopted into the business process that has been approved by PTDI as a series of improvements to the business process. In addition to having an impact on the existing business system, this case study also suggests that PTDI increase knowledge to the Project Manager to have training in accordance with the principles of Project Management. in collaboration with HRD, the proposed training will be scheduled as a means of increasing PTDI's resources.Keyword: Project Management, CN295, PMBOK, Current Reality Tree, Customizing Medium Aircraft